2022
DOI: 10.1002/cbdv.202200925
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Design and Investigation of Novel Thiazetidine Derivatives as Potent Inhibitors of PrpR in Mycobacterium tuberculosis

Abstract: Tuberculosis is one of the most life‐threatening acute infectious diseases diagnosed in humans. In the present investigation, a series of 16 new disubstituted 1,3‐thiazetidines derivatives is designed, and investigated via various in silico methods for their potential as anti‐tubercular agent by evaluating their ability to block the active site of PrpR transcription factor protein of Mycobacterium tuberculosis. The efficacy of the molecules was initially assessed with the help of AutoDock Vina algorithm. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The value of aqueous solubility (QPlogS) should be between −6.5 to 0.5. Table 3 shows the results of ADME analysis [33] . All the proposed molecules are satisfactorily within the above limits and therefore are identified as hit molecules for further analyses.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The value of aqueous solubility (QPlogS) should be between −6.5 to 0.5. Table 3 shows the results of ADME analysis [33] . All the proposed molecules are satisfactorily within the above limits and therefore are identified as hit molecules for further analyses.…”
Section: Resultsmentioning
confidence: 74%
“…Table 3 shows the results of ADME analysis. [33] All the proposed molecules are satisfactorily within the above limits and therefore are identified as hit molecules for further analyses. QPPCaCo is the predicted Caco-2 cell permeability rate.…”
Section: Adme Propertiesmentioning
confidence: 84%
“…Maintaining our pursuit of investigating the possible uses of bioactive compounds produced via a sustainable route for therapeutic application [56][57][58][59][60][61], herein, we report the ionic liquid-supported copper-catalyzed synthesis of 2H-indazoles under microwaves through the sequential formation of C-N and N-N bonds. The synthetic methods reported in this article include comprehensive details on the formation of the ionic liquid-supported copper catalyst as well as its catalytic application for the preparation of 2H-indazoles.…”
Section: Introductionmentioning
confidence: 99%
“…18,21,28 In diagnostic and theranostic research, many luminescent probes have been reported to sense a variety of biological, chemical and environmental analytes but there are still challenges with tuning the luminescence properties of these probes. 29,30 Similarly, the roles of thiazetidines, quinolines and fused imidazoquinolines towards anti-cancer and anti-microbial properties were explored through computational methods, 31,32 but there are limitations in synthesizing these structures; Click chemistry can be employed to overcome these drawbacks. Although some issues exist with the reactivity of Click reactants, efforts to overcome these are underway, particularly for applications like direct conjugation, 19,33 induced drug release and delivery of gaseous signalling molecules.…”
Section: Introductionmentioning
confidence: 99%